Interactions between environmental factors and maternal–fetal genetic variations: strategies to elucidate risks of preterm birth. (July 2016) - Pereyra, Silvana; Bertoni, Bernardo; Sapiro, Rossana
Abstract: Context: Preterm birth (PTB) is a complex disease in which medical, social, cultural, and hereditary factors contribute to the pathogenesis of this adverse event. Interactions between genes and environmental factors may complicate our understanding of the relative influence of both effects on PTB. To overcome this, we combined data obtained from a cohort of newborns and their mothers with multiplex analysis of inflammatory-related genes and several environmental risk factors of PTB to describe the environmental–genetic influence on PTB. Objective: The study aimed to investigate the association between maternal and fetal genetic variations in genes related to the inflammation pathway with PTB and to assess the interaction between environmental factors with these variations. Study design: We conducted a case–control study at the Pereira Rossell Hospital Center, Montevideo, Uruguay. The study included 143 mother–offspring dyads who delivered at preterm (gestational age < 37 weeks) and 108 mother–offspring dyads who delivered at term. We used real-time PCR followed by a high-resolution melting analysis to simultaneously identify gene variations involved in inflammatory pathways in the context of environmental variables. The genes analyzed were: Toll-like receptor 4 (TLR4), Interleukin 6 (IL6), Interleukin 1 beta (IL1B) and Interleukin 12 receptor beta (IL12RB). Results: We detected a significant interaction between IL1B rs16944 polymorphism in maternal samples and IL6 rs1800795 polymorphism in newborns, emphasizing the role of the interaction of maternal and fetal genomes in PTB. In addition, smoke exposure and premature rupture of membranes (PROM) were significantly different between the premature group and controls. IL1B and IL6 polymorphisms in mothers were significantly associated with PTB when controlling for smoke exposure. TLR4 polymorphism and PROM were significantly associated with PTB when controlling for PROM, but only in the case of severe PTB. Conclusions: Interactions between maternal and fetal genomes may influence the timing of birth. By incorporating environmental data, we revealed genetic associations with PTB, a finding not found when we analyzed genetic data alone. Our results stress the importance of studying the effect of genotype interactions between mothers and children in the context of environmental factors because they substantially contribute to phenotype variability.